Developing a prediction model for disease‐free survival from upper urinary tract urothelial carcinoma in the Korean population. (8th July 2019) - Kim, Sung Han; Song, Mi Kyung; Hong, Bumsik; Kang, Seok Ho; Jeong, Byong Chang; Ku, Ja Hyun; Seo, Ho Kyung
Abstract: Background: In this study, we aimed to propose a validated prediction model for disease‐free survival (DFS) after radical nephroureterectomy (RNU) in a Korean population with upper urinary tract urothelial carcinoma (UTUC). Methods: We performed a retrospective review of 1561 cases of UTUC who underwent either open RNU (ONU, n = 906) or laparoscopic RNU (LNU, n = 615) from five tertiary Korean institutions between January 2000 and December 2012. Data were used to develop a prediction model using the Cox proportional hazards model. Prognostic factors were selected using the backward variable selection method. The prediction model performance was investigated using Harrell's concordance index (C‐index) and Hosmer‐Lemeshow type 2 statistics. Internal validation was performed using a bootstrap approach, and the National Cancer Center data set (n = 128) was used for external validation. Results: A best‐fitting prediction model with seven significant factors was developed. The C‐index and two Hosmer‐Lemeshow type statistics of the prediction model were 0.785 (95% CI, 0.755‐0.815), 4.810 ( P  = 0.8506), and 5.285 ( P  = 0.8088). The optimism‐corrected estimate through the internal validation was 0.774 (95% CI, 0.744‐0.804) and the optimism‐corrected calibration curve was close to the ideal line with mean absolute error = 0.012. In external validation, the discrimination was 0.657 (95% CI, 0.560‐0.755) and the two calibration statistics were 0.790 ( P  = 0.9397) and 3.103 ( P  = 0.5408), respectively. Conclusion: A validated prediction model based on a large Korean RNU cohort was developed with acceptable performance to estimate DFS in patients with UTUC. Abstract : Upper urinary tract urothelial carcinomas (UTUC) are rare; however, the incidence is slowly increasing. Despite radical nephroureterectomy, the prognosis of patients with UTUC is poor. This large multicenter Korean cohort study makes a significant contribution to the literature because our user‐friendly prediction nomogram of 3‐year disease‐free survival of UTUC, which is based on seven clinicopathological factors, could help to estimate prognosis and select appropriate treatment.